Strategi Komunikasi Pemasaran Digital Toko GreenGO melalui Marketplace TikTok - Ayunda Maiza; Ade Budi Santoso (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The rapid development of information technology has profoundly influenced the transformation of marketing communication in the digital era. One of the most significant innovations in recent years is TikTok, a social media platform that has evolved into a powerful marketplace for business actors. This study aims to analyze the digital marketing communication strategy implemented by GreenGO Store through TikTok Shop, using the AIDA theory (Awareness, Interest, Desire, Action) as an analytical framework. The study employs a qualitative descriptive approach, with data collected through in-depth interviews involving three key informants: the head of digital marketing, TikTok live admin, and online shop admin. The findings reveal that GreenGO’s communication strategy successfully attracts audience attention (awareness) through creative content, fosters interest via two-way interaction during live streaming, creates desire through emotional storytelling and trend-based promotions, and drives purchasing actions through discount strategies and ease of transaction. This strategy not only boosts sales performance but also enhances customer loyalty and strengthens the eco-friendly brand image.